Impact of urinary PAHs on psoriasis risk in U.S. adults: Insights from NHANES. - Jiang-Hui Li; Xiao-Ning Yan; Jia-Ying Fu; Hao-Yuan Hu (PLoS ONE)
Objective Exposure to environmental pollutants is increasingly recognized as a risk factor for the development of psoriasis. Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous in the air and might induce reactions such as oxidative stress. Nevertheless, it is still unclear if PAHs have any influence on the prevalence of psoriasis over the entire population of the United States. The objective of this study was to assess the association between urine PAHs and psoriasis. Methods The research included 3,673 individuals aged 20 years or older who participated in the 2003-2006 and 2009-2012 National Health and Nutrition Examination Surveys (NHANES). We employed logistic regression models to evaluate the relationship between levels of urine PAH metabolites and psoriasis and smoothed curve fitting to illustrate the concentration-response relationship. Additionally, subgroup and interaction analyses were conducted to elucidate these associations. Furthermore, we employed weighted quartile sum (WQS) regressions to examine the distinct effects of individual and mixed urine PAH metabolites on psoriasis. However, it is important to note that the NHANES sample may be subject to selectivity and self-reporting bias, which may influence the data' generalisability. Results We observed that the highest tertiles of 2-NAP and 2-FLU had a 63% (95% CI 1.02, 2.61) and 83% (95% CI 1.14, 2.96) higher odds of association with psoriasis prevalence, respectively. Meanwhile, tertile 2 and tertile 3 of 3-PHE were also significantly associated with psoriasis, with higher odds of 65% (95% CI 1.01, 2.69) and 14% (95% CI 1.17, 3.00), respectively. The subgroup analyses revealed a significant correlation between urine PAH metabolites and the odds of psoriasis in specific groups, including males, aged 40-60 years, with a BMI > 30, and those with hyperlipidemia. In the WQS model, a positive association was found between the combination of urine PAH metabolites and psoriasis (OR 1.43, 95% CI 1.11, 1.84), with 2-FLU being the most prevalent component across all mixtures (0.297). Conclusions Our findings indicate a significant association between urine PAH metabolites and the odds of psoriasis prevalence in adults. Among these metabolites, 2-FLU demonstrated the most prominent impact. Controlling PAH exposure, as an important strategy for minimizing exposure to environmental contaminants and lowering the risk of psoriasis, is critical for raising public knowledge about environmental health and preserving public health.